Determination of Maintenance Task on Rotary Equipment Using Reliability Centered Maintenance II Method - Priyanta, Dwi; Siswantoro, Nurhadi; Sukandar, Rizky Agung (International Journal of Marine Engineering Innovation and Research, 2025)
The process of natural gas into LNG (Liquefied Natural Gas) requires many steps and various types of chemical products. The process also produces waste. The Liquid Incinerator treats waste from LNG process. This unit often experiences damages which causes the plant do not work properly and even a down/trip problems due to the continuous operation and the absence of maintenance program, especially for rotary equipments. This causes environmental pollution because the waste is unprocessed and could have an impact on the increased cost to treat the waste elsewhere. One of approaches to analyze the causes of the damage, the impact and effective treatment for equipment is using Reliability Centered Maintenance (RCM). The RCM method is expected to be able to identify the primary and secondary functions of the system, possible failure function, Failure Mode and Effect Analysis (FMEA), and the maintenance actions on the plant. The FMEA result will be used to determine the proposed maintenance task. Based on the proposed maintenance task, the maintenance interval for each equipment is obtained. After RCM analysis is done on 4 equipments, liquid waste feeding pump (34-G-2), quencher pump (34-G-3), scrubber pump (34-G-4) and air compressor (34-K-4). For 34-G-2 failure mode, requires 78% preventive maintenance and 22% corrective maintenance, 34-G-3 requires 87% preventive maintenance and 13% corrective maintenance, 34-G-4 requires 87% preventive maintenance and 13% corrective maintenance and 34-K-4 requires 70% preventive maintenance and 30% corrective maintenance. Workpackage for each interval is created from every failure mode for each interval for maintenance / inspection.